Perilaku Remaja Putri dan Kejadian Flour Albus - Siska Milya Anggraini; Firdawsyi Nuzula; Haswita Haswita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Flour albus in adolescent girls usually occurs due to lack of knowledge about preventive behavior. Fluor albus that occurs continuously can cause diseases that require special treatment. This study aims to determine the effect of knowledge and behavior of adolescent girls on the incidence of flour albus. The design of this study was cross-sectional. The research subjects were 80 adolescent girls who were selected by total population sampling technique. Data were collected through filling out a questionnaire, then analyzed using logistic regression test. The results of data analysis showed that the p-value for knowledge and behavior were 0.926 and 0.000, respectively. Thus, it is concluded that the incidence of fluor albus is influenced by the behavior of adolescent girls.Keywords: flour albus; behavior; adolescent girls ABSTRAK Flour albus pada remaja biasanya terjadi karena kurangnya pengetahuan tentang perilaku pencegahannya. Flour albus yang terjadi secara terus-menerus dapat menimbulkan penyakit yang memerlukan penanganan khusus. Penelitian ini bertujuan mengetahui pengaruh pengetahuan dan perilaku remaja putri terhadap kejadian flour albus. Rancangan penelitian ini adalah cross-sectional. Subyek penelitian adalah 80 remaja putri yang dipilih dengan teknik total population sampling. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji regresi logistik. Hasil analisis data menunjukkan bahwa nilai p untuk pengetahuan dan perilaku, masing-masing adalah 0,931 dan 0,000. Dengan demikian disimpulkan bahwa kejadian fluor albus dipengaruhi oleh perilaku remaja putri. Kata kunci: flour albus; perilaku; remaja putri